2014
DOI: 10.7202/1025905ar
|View full text |Cite
|
Sign up to set email alerts
|

La réforme des soins primaires de santé mentale au Québec et le rôle et les stratégies de coordination des omnipraticiens

Abstract: Les systèmes sociosanitaire et de santé mentale au Québec ont été substantiellement transformés dans les dernières années. Au coeur des restructurations, les réformes ont visé la consolidation des soins primaires et une meilleure intégration du dispositif de soins, tendances centrales des réformes sur le plan international. Cet article résume les principaux axes de transformation des réformes du système sociosanitaire et de la santé mentale au Québec. Il présente aussi le rôle clé des omnipraticiens dans la pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
(29 reference statements)
0
3
0
2
Order By: Relevance
“…In terms of enabling factors influencing high ED use only, previous research confirms that prior high ED use for MD and/or SRD is often associated with recurrent ED use, defined as ED use over several years (Hansagi et al, 2012;Kanzaria et al, 2017). Reasons for choosing ED services over ambulatory care may be related to satisfaction with prior ED treatment (Fortin et al, 2018;Ruud et al, 2016), difficulties accessing ambulatory care (Ayangbayi et al, 2017;Nesper et al, 2016), stigmatization in ambulatory care (Keyes et al, 2010;van Boekel et al, 2015), and underfunding of SUD programs (Fleury et al, 2016b) or of integrated treatment for SUD/MD (Fleury, 2014). Primary care physicians are often reluctant to follow such patients (Ross et al, 2015;van Boekel et al, 2015), previously identified as treatment resistant (Edlund et al, 2009;Mojtabai and Crum, 2013), and presenting multiple psychosocial problems (Khan, 2017;Moulin et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…In terms of enabling factors influencing high ED use only, previous research confirms that prior high ED use for MD and/or SRD is often associated with recurrent ED use, defined as ED use over several years (Hansagi et al, 2012;Kanzaria et al, 2017). Reasons for choosing ED services over ambulatory care may be related to satisfaction with prior ED treatment (Fortin et al, 2018;Ruud et al, 2016), difficulties accessing ambulatory care (Ayangbayi et al, 2017;Nesper et al, 2016), stigmatization in ambulatory care (Keyes et al, 2010;van Boekel et al, 2015), and underfunding of SUD programs (Fleury et al, 2016b) or of integrated treatment for SUD/MD (Fleury, 2014). Primary care physicians are often reluctant to follow such patients (Ross et al, 2015;van Boekel et al, 2015), previously identified as treatment resistant (Edlund et al, 2009;Mojtabai and Crum, 2013), and presenting multiple psychosocial problems (Khan, 2017;Moulin et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…MH systems in developed countries (United Kingdom, Australia, Belgium, etc.) have undergone major transformation in recent decades aimed at improving overall performance [711], primary care [12, 13], service integration [14, 15], care continuity [16], and in adopting multidisciplinary teams, and recovery best-practices (e.g. care pathways, intensive case management, assertive community treatment) [1719].…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the lack of access to primary care physicians in rural regions, with ratios of physicians per capita being between 30 to 50% greater in major urban centres compared to other regions [ 40 ], a situation that has barely evolved over the past 20 years [ 49 ]. General practitioners in rural areas may be especially overwhelmed and not able/willing to treat severe mental illnesses [ 50 ], preferring to refer to psychiatric care [ 51 , 52 ]. Community psychosocial services are also lacking outside urban areas [ 53 ], which may result in a greater involvement of medical professionnals.…”
Section: Discussionmentioning
confidence: 99%